Capability development and management R&D professionals in a developing context, Taiwan - Hsiao, Ta-Cheng (Technovation)
Confucian moral values are considered with regard to their influence on personality within the R&D sector of Taiwan's industry. The study uses its own inventory, and twelve R&D institutions in Taiwan were the basis of various conclusions drawn.